Long-term effects of a maternal high-fat: high-fructose diet on offspring growth and metabolism and impact of maternal taurine supplementation. (18th August 2020) - Li, M.; Reynolds, C. M.; Gray, C.; Patel, R.; Sloboda, D. M.; Vickers, M. H.
Abstract: Objective: Maternal obesity is associated with obesity and metabolic disorders in offspring. However, there remains a paucity of data on strategies to reverse the effects of maternal obesity on maternal and offspring health. With maternal undernutrition, taurine supplementation improves outcomes in offspring mediated in part via improved glucose–insulin homeostasis. The efficacy of taurine supplementation in the setting of maternal obesity on health and well-being of offspring is unknown. We examined the effects of taurine supplementation on outcomes related to growth and metabolism in offspring in a rat model of maternal obesity. Design: Wistar rats were randomised to: 1) control diet during pregnancy and lactation (CON); 2) CON with 1.5% taurine in drinking water (CT); 3) maternal obesogenic diet (MO); or 4) MO with taurine (MOT). Offspring were weaned onto the control diet for the remainder of the study. Results: At day 150, offspring body weights and adipose tissue weights were increased in MO groups compared to CON. Adipose tissue weights were reduced in MOT versus MO males but not females. Plasma fasting leptin and insulin were increased in MO offspring groups but were not altered by maternal taurine supplementation. Plasma homocysteine concentrations were reduced in all maternal taurine-supplemented offspring groups. There were significant interactions across maternal diet, taurine supplementation and sex for response to an oral glucose tolerance test, a high-fat dietary preference test and pubertal onset in offspring. Conclusions: These results demonstrate that maternal taurine supplementation can partially ameliorate adverse developmental programming effects in offspring in a sex-specific manner.